2020
DOI: 10.1186/s12872-019-01310-5
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-oxide has prognostic value in coronary heart disease: a meta-analysis and dose-response analysis

Abstract: Background: Previous clinical studies have suggested that trimethylamine-N-oxide (TMAO) could contribute to the development of atherosclerosis cardiovascular disease. However, the synthetic analysis in coronary heart disease (CHD) was not yet performed. We aimed to clarify the relationship between elevated plasma concentrations of TMAO and the incidence of major adverse cardiovascular events (MACE) in CHD patients. Methods: Meta-analysis and dose-response analysis of hazard ratio data from prospective observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 40 publications
1
51
3
1
Order By: Relevance
“…In our study plasma TMAO was negatively associated with the presence of soft plaque, total plaque burden, and calcified plaque burden in univariate and multivariable models after adjusting for age, sex, and traditional risk factors. Whilst this finding contrasts with some prior studies that have found TMAO is associated with increased incidence of major adverse cardiovascular events in patients with established CAD, peripheral artery disease or chronic kidney disease, it is in keeping with other studies that have not confirmed an association with CAD and have suggested there may be a more nuanced relationship [ 39 , 40 , 41 ]. TMAO is generated through the oxidation of trimethylamine (TMA) by TMA monooxygenase present in some gut microbiota [ 42 ].…”
Section: Discussioncontrasting
confidence: 84%
“…In our study plasma TMAO was negatively associated with the presence of soft plaque, total plaque burden, and calcified plaque burden in univariate and multivariable models after adjusting for age, sex, and traditional risk factors. Whilst this finding contrasts with some prior studies that have found TMAO is associated with increased incidence of major adverse cardiovascular events in patients with established CAD, peripheral artery disease or chronic kidney disease, it is in keeping with other studies that have not confirmed an association with CAD and have suggested there may be a more nuanced relationship [ 39 , 40 , 41 ]. TMAO is generated through the oxidation of trimethylamine (TMA) by TMA monooxygenase present in some gut microbiota [ 42 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Three recent meta-analyses have established that elevated TMAO blood levels are related with increased CVD risks and all-cause mortality [98,102,103], nevertheless, some criticism exists about the TMAO and CVD relationship because fish could contain high concentrations of TMAO and TMA [104]. However, fish consumption is related with heart health [105][106][107].…”
Section: Diet Gut Microbiota and Cardiovascular Diseasesmentioning
confidence: 99%
“…Surprisingly, TML levels were only 0.47 µmol/L in acute stroke patients and significantly lower compared with healthy controls. Our findings argue against a linear relationship of TML with vascular disease, but rather suggests a J-shaped relationship similar to TMAO with MACE (Yao et al 2020). Although we also observed higher TML levels in acute stroke patients with prevalent cardiovascular disease, the mean TML level for all patients with cerebral ischemia are of the lowest reported, so far.…”
Section: Discussionmentioning
confidence: 52%